EFFECTIVENESS OF BUILDING PERMIT SERVICES IN ESTABLISHING AN ORDER OF BUILDING PLANS AT THE ONE DOOR INVESTMENT SERVICE IN THE CITY OF BANDAR LAMPUNG - Sinta Apriyani (DEMOKRASI, 2023)
There are still many people who are disobedient and reluctant to apply for permits, even though the permit service process at the Investment and One-Stop Services Office of Bandar Lampung City has provided easy service. The method in this study uses a literature review. Data sources use secondary data sources in the form of documents, laws and regulations, articles and books. This is because there are still many people who think that licensing is like the old pattern which is difficult and convoluted. From the results of research by researchers in the field, in the city of Bandar Lampung, there is in the Antasari area in the city of Bandar Lampung, where there is a food and beverage business by constructing buildings without a building permit (IMB), and this trading business license (SIUP) is one of the inhibiting factors. in licensing services. This problem is of course a concern for the Investment Service and One Stop Integrated Services of Bandar Lampung City to provide understanding and outreach to all elements of the Bandar Lampung City community that the permit service process at DPMPTSP provides easy, accountable, friendly, fair, simple, sympathetic services and safe.Â  Â